Enhancement of the Stability and Anti-DPPIV Activity of Hempseed Hydrolysates Through Self-Assembling Peptide-Based Hydrogels - Lammi, Carmen; Bollati, Carlotta; Gelain, Fabrizio; Arnoldi, Anna; Pugliese, Raffaele (Frontiers in Chemistry, 2019)
Although there is an increasing interest for bioactive food protein hydrolysates as valuable ingredients for the functional food and dietary supplement formulations, their potential applications are hampered by their insufficient stability in physiological conditions. In this work, an innovative strategy based on nanomaterials was developed in order to increase the hempseed hydrolysate stability and the anti-diabetic properties, through their encapsulation into ionic self-complementary RADA16 peptide based-hydrogels. Atomic force microscope morphological analysis indicated that the new nanomaterials were composed of a nanofibril network, whose increased diameter in respect to native RADA16 suggests the presence of transient non-covalent interactions among the RADA16 supramolecular assemblies and the embedded hempseed peptides. Structural analysis by FT-IR spectroscopy indicated typical β-sheet signatures. The RADA16-hempseed protein hydrolysate hydrogel was shown to act as a novel dipeptidyl peptidase IV (DPPIV) inhibitor in different biological assay. Finally, this nano-formulation was used as a drug delivery system of the antidiabetic drug sitagliptin, helping to reduce its dosage and eventually associated side-effects.